New Bioactive Fused Triazolothiadiazoles as Bcl-2-Targeted Anticancer Agents - Rania Hamdy (MDPI AG, 2021)
A series of 3-(6-substituted phenyl-[1,2,4]-triazolo[3,4-b]-[1,3,4]-thiadiazol-3-yl)-1H-indoles (5a–l) were designed, synthesized and evaluated for anti-apoptotic Bcl-2-inhibitory activity. Synthesis of the target compounds was readily accomplished through a reaction of acyl hydrazide (1) with carbon disulfide in the presence of alcoholic potassium hydroxide to afford the corresponding intermediate potassium thiocarbamate salt (2), which underwent cyclization reaction in the presence of excess hydrazine hydrate to the corresponding triazole thiol (3). Further cyclisation reaction with substituted benzoyl chloride derivatives in the presence of phosphorous oxychloride afforded the final 6-phenyl-indol-3-yl [1,2,4]-triazolo[3,4-b]-[1,3,4]-thiadiazole compounds (5a–l). The novel series showed selective sub-micromolar IC50 growth-inhibitory activity against Bcl-2-expressing human cancer cell lines. The most potent 6-(2,4-dimethoxyphenyl) substituted analogue (5k) showed selective IC50 values of 0.31–0.7 µM against Bcl-2-expressing cell lines without inhibiting the Bcl-2-negative cell line (Jurkat). ELISA binding affinity assay (interruption of Bcl-2-Bim interaction) showed potent binding affinity for (5k) with an IC50 value of 0.32 µM. Moreover, it fulfils drug likeness criteria as a promising drug candidate.